A Simple and Sensitive Method for Determination of Sugar Content in Fruits and Culture Media During Fermentation - Djagal Wiseso Marseno; Retno Indrati (agriTECH, 2009)
A colorimetric for sugar determination using cuprammonium reagent containing strong base has been improved with a heating process after a reaction started.  The reaction was started after the sugar or sample containing sugar was added to the cuprammonium reagent consisted of 1 mM CuSO – 0,4 M (NH ) SO – 0,6 M NaOH).  This heat ing process could enhance the formation of sugarcupper ammonium complex, so that the intensity of absorbance increased at wavelength of 280 nm. This simple and sensitive method was applicable for various sugars detection such as sugar fraction after HPLC separation, sugar content in biological extract or in culture medium during fermentation. Interestingly, different from previous report, this method was specific for non polyol sugars.